Upaya Guru Bidang Studi Aqidah Akhlak dalam Membina Akhlak Siswa Kelas VI Madrasah Ibtidaiyah Darul Falah 2 Cilodong - Depok - Hadiyanti Dini Islamiati, Siti; Syarif, Ahmad; Suryati, Yeti; Nuraini, Rulita; Yulianti, Murni (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is driven by the bad impact of the digital world on the learning process, which spontaneously affects students' attitudes and behaviors. One of these impacts is students' social attitudes. The study examines the crucial role of teachers in the Aqidah Akhlak subject in instilling moral values in sixth-grade students at MI Darul Falah 2 Cilodong, Depok. Data collection methods included observation, interviews, and documentation of activities, which were then assessed descriptively. The outcomes of the teaching methods utilized by the teachers can be drawn in the changes in students' attitudes and the way teachers teach Aqidah Akhlak. These changes are evident from students' discipline towards school rules, the habituation practices applied in the classroom, and the exemplary actions of the teachers as models for students to follow. The study concludes that teachers' understanding of their crucial role through workshops, training, and seminars on moral education strategies is effective in promoting the utilize of innovative teaching methods such as interactive lectures, role-playing, and extracurricular activities to instill positive character traits. Collaboration between schools, parents, and the community is also deemed essential for effectively monitoring and supporting students' moral development. Continuous evaluation of moral education efforts involving students, parents, and school authorities is crucial for enhancing the quality of moral education in the future. Overall, this research aims to foster a generation with strong character and noble behavior through the dedicated efforts of teachers in the Aqidah Akhlak subject.